Anemia and functional capacity in elderly Brazilian hospitalized patients - Raquel de Macedo Bosco; Elisa Priscila Souza Assis; Renata Rosseti Pinheiro; Luiza Cristina Viana de Queiroz; Leani S. M. Pereira; Carlos Maurício Figueiredo Antunes (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
This study evaluated the association between anemia and physical functional capacity in a cross-sectional population-based sample of 709 hospitalized elderly patients aged 60 years and over admitted to the Madre Teresa Hospital, Belo Horizonte, State of Minas Gerais, Brazil. The Mann-Whitney or "t" test, and chi-square or Fisher exact test were used for quantitative and categorical variables, respectively, and hierarchical binary logistic regression was used to identify significant predictors. The presence of anemia was found in 30% of participants and was significantly associated with decreased functionality according to the two measures which were used - ADL (activities of daily living) and IADL (instrumental activities of daily living). Anemia was also independently associated with older age. The results of this study demonstrate a strong association between the presence of anemia and lower levels of functional capacity. Further investigations are needed to assess the impact of anemia treatment on the functionality and independence of older people.